Poverty Estimates of Agro-Climatic Subregions - Planning Commission (Planning Commission, 1990)
In this paper poverty estimates in Agro climatic zones and subzones are presented using alternative poverty lines. NSS has tabulated, for 38 round(1983-84) the distribution of population by monthly per capita expenditure classes(MPCE) by zones as well as by divisions, separately for rural and urban regions.
Agro-Climatic Regional Planning Unit Planning Commission
Agro Climatic Regional Planning Unit Planning Commission